DINAMIKA POPULASI ANJING DAN PENGARUHNYA TERHADAP CAKUPAN VAKSINASI RABIES DI RURAL DAN URBAN KABUPATEN SIKKA PADA BULAN OKTOBER 2009 - APRIL 2010 - , drh. Maria Margaretha Siko; , drh. Heru Susetya, MP., PhD ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Rabies mass vaccination have been conducted annually in Sikka Regency since 2001. With minimal 70% of vaccination coverage for few years it was targeted Sikka (Flores) would be eradicated from rabies on 2005. This target could not be reach even the bite cases tend to increase with the increasing of dog population. This study was conducted to provived the basic information about dog population and to know the impact of dog population dynamic toward the vaccination coverage at one blow to evaluated the failure of vaccination program by the perspective of population. The study was conducted by the clusters survey. The regency was stratified into rural and urban. From each stratum, 7 subdistricts (desa or kelurahan) are chosen proportionally using systematic random sampling. From each kelurahan or desa that has been choosen, one dusun or rw was taken as a cluster by using simple random sampling. Household survey was conducted since October 2009 to April 2010 in interval of two months. Overall 1321 household 442 household in rural and 879 in urban area. Owned dog ratio 1:1.5 in rural with average 2.7 per household and 1:3.8 in urban with average 2.5 per household. Dog human ratio was 1:2.4 and 1:8.3, dog density was 233.30±53.78 per km2 and 321.05±50.65 per km2 in rural and urban respectively. A high percentage of owned dogs was always allowed to roam freely (99.65% in rural and 92.69% in urban). Dog accessibility was 94.81% and 98.03% in rural and urban, respectively. Population structure was dominated by 0-3 month of age (28.01% in rural and 33.88% in urban). There was a predominance of female dogs with ratio 1.59:1 in rural and 1.61:1 in urban area. Dog litter size was 3.76±0,11 in rural and 4,90±0,19 urban. The peak of birth was November- December in rural and March-April in urban. Dog migration from rural to urban was 36.7% on the contrary from urban to rural was 1.2%. Vaccination coverage decreased from 32.56% on October 2009 to 25.06% on April 2010 and 32.90% on October 2009 to 16.34% on April 2010, for rural and urban area, respectively. From this research we concluded that dog population dynamic decreased rabies vaccination coverage.